Challenges and benefits of using NOx as a quantitative proxy for fossil fuel CO2 in an urban area based on radiocarbon measurements - Juchem, Hannes; Maier, Fabian; Levin, Ingeborg; Jordan, Armin; Pöhler, Denis; Rosendahl, Claudius; Della Coletta, Julian; Preunkert, Susanne; Hammer, Samuel (Atmospheric chemistry and physics, 2025)
Radiocarbon (14CO2) observations are the benchmark for quantifying fossil fuel CO2 (ffCO2) in the atmosphere, but continuous 14CO2 measurements are not yet available. Continuous estimates of ffCO2 can be made by observing continuously measurable proxies that are co-emitted during fossil fuel combustion. This paper investigates the potential and challenges of using in situ NOx observations in urban areas to quantitatively estimate hourly ffCO2 enhancements, in the example of the ICOS pilot station in Heidelberg, Germany. The short atmospheric lifetime of NOx limits the use of the observed signal to a local area. Thus, a local NOx and ffCO2 background was approximated using the Stochastic Time-Inverted Lagrangian Transport (STILT) model and bottom-up emission estimates from the Netherlands Organisation for Applied Scientific Research (TNO). Using 14CO2 data from 185 hourly integrated flask samples between 2020-2021, mean ratios of local excess NOx (ΔNOx) to local excess ffCO2 (ΔffCO2) of 1.40 ppb ppm−1 for winter and 2.12 ppb ppm−1 for summer were calculated. These ratios were applied to the ΔNOx time series to construct continuous ΔffCO2 estimates. The uncertainty of the ΔNOx-based ΔffCO2 record was estimated at 3.94 ppm. Comparisons with 14CO2-based and ΔCO-based ΔffCO2 estimates showed good agreement, while still demonstrating distinct behaviour for individual events. ΔNOx shows considerable potential as ΔffCO2 proxy and as useful addition to ΔCO-based estimates, as both proxies have different footprints due to their lifetimes. A key challenge remains in reliably determining the seasonal and diurnal cycle of average ΔNOx to ΔffCO2 ratios.
Veröffentlicht: 17. Dezember 2025
Gesehen am 06.02.2026
Im Titel sind der Buchstabe "x" sowie die Zahl 2 tiefgestellt